Study of the mechanism of action of anoplin, a helical antimicrobial decapeptide with ion channel-like activity, and the role of the amidated C-terminus - Dos Santos Cabrera, Marcia Perez; Arcisio-Mirandaa, Manoel; Broggio Costa, Sabrina Thais [UNESP]; Konno, Katsuhiro; Ruggiero, José Roberto [UNESP]; Procopio, Joaquim; Neto, Joao Ruggiero [UNESP] (John Wiley & Sons Ltd, 2008)
Anoplin, an antimicrobial, helical decapeptide from wasp venom, looses its biological activities by mere deamidation of its C-terminus. Secondary structure determination, by circular dichroism spectroscopy in amphipathic environments, and lytic activity in zwitterionic and anionic vesicles showed quite similar results for the amidated and the carboxylated forms of the peptide. The deamidation of the C-terminus introduced a negative charge at an all-positive charged peptide, causing a loss of amphipathicity, as indicated by molecular dynamics simulations in TFE/water mixtures and this subtle modification in a peptide's primary structure disturbed the interaction with bilayers and biological membranes. Although being poorly lytic, the amidated form, but not the carboxylated, presented ion channel-like activity on anionic bilayers with a well-defined conductance step; at approximately the same concentration it showed antimicrobial activity. The pores remain open at trans-negative potentials, preferentially conducting cations, and this situation is equivalent to the interaction of the peptide with bacterial membranes that also maintain a high negative potential inside. Copyright (C) 2007 European Peptide Society and John Wiley & Sons, Ltd.
Keywords: Anoplin; Antimicrobial peptide; Lytic activity; Ion channel; Pore activity; Peptide-membrane interaction; Molecular dynamics